Effect of Giving Turmeric Rhizome and Teak Leaves Combination on Egg Quality and Productivity of Laying Hens - Harlita, Harlita; Solikhah, Inayatu (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
This research was conducted to study the effect of feeding additives in the form of a combination of turmeric rhizome (Curcuma longa) and teak leaf (Tectona grandis) on egg quality and productivity of laying hens. The method used in this research is an experimental method with a completely Randomized Design (CRD). The study used one control group (P0) and three treatment groups. The treatment group was given feed additives in drinking water in the form of a combination of turmeric rhizome and teak leaves at intervals of once a day (P1), once every two days (P2), and once every four days (P3). The study was conducted on light-type laying hens aged about 72 weeks for 28 days. The data was obtained in the form of size and weight of eggs and egg production. Data on the size and weight of eggs were obtained by measuring the circumference and weight of the eggs, while data on egg productivity was obtained by calculating the number of chicken eggs produced each day. Data analysis with One Way Anova using SPSS 23 program. The results showed that egg quality was not significantly different but the provision of feed additives at intervals of once a day resulted in the highest average egg size and egg production.